Влияние гендерного статуса женщин на психофармакотерапию алкогольной зависимости = Influence of gender status of women alcohol dependence on psychopharmacotherapy - Ryabuhin, K. V. (Journal of Education, Health and Sport, 2015)
Ryabuhin K. V. Влияние гендерного статуса женщин на психофармакотерапию алкогольной зависимости = Influence of gender status of women alcohol dependence on psychopharmacotherapy. Journal of Education, Health and Sport. 2015;5(9):170-182. ISSN 2391-8306. DOI10.5281/zenodo.30520 http://dx.doi.org/10.5281/zenodo.30520 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A170-182 https://pbn.nauka.gov.pl/works/619555 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.07.2015. Revised 24.08.2015. Accepted: 29.08.2015. УДК: 616-056.83:613.816 ВЛИЯНИЕ ГЕНДЕРНОГО СТАТУСА ЖЕНЩИН НА ПСИХОФАРМАКОТЕРАПИЮ АЛКОГОЛЬНОЙ ЗАВИСИМОСТИ Influence of gender status of women ALCOHOL DEPENDENCE ON psychopharmacotherapy К. В. Рябухин K. V. Ryabuhin Одесский национальный медицинский университет Odessa National Medical University Summary The article, based on the system of scientific research, clinical observations, and set of integrated research given characteristic of specific disharmonious clinical and psychological characteristics of alcohol dependence in women, established the basic biological, personality and psychosocial predictors of alcohol dependence in women, identify and characterize the main groups of pathological consequences of female alcohol addiction, to develop and implement measures psycho pharmaco- and psychotherapy for alcohol dependence in women, taking into account peculiarities of gender status. Keywords: alcohol dependence, major predictors of alcohol dependence in women, psychopharmacotherapy. Резюме В статье, на основе системного научного исследования, клинических наблюдений и комплекса интегрированных исследований предоставлено характеристику специфических дисгармоничных клинико-психологических особенностей алкогольной зависимости у женщин, установлено основные биологические, личностные и психосоциальные предикторы, алкогольной зависимости у женщин, определено и охарактеризовано основные группы патологических последствий женской алкогольной зависимости, разработаны и внедрены мероприятия психофармако- и психотерапии алкогольной зависимости у женщин с учетом особенностей гендерного статуса. Ключевые слова: алкогольная зависимость, основные предикторы алкогольной зависимости у женщин, психофармакотерапия.